2014
DOI: 10.1186/2196-4351-2-16
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a bonding agent and thermo-mechanical cycling on the bond strength of a glass-ceramic to gold and cobalt-chromium alloys

Abstract: To evaluate the effects of bonding agent and thermo-mechanical cycling on the flexural bond strength of a gold and cobalt-chromium alloy to a feldspathic ceramic. Sixty-four metal bars were fused (3 × 25 × 0.5 mm 3 ): 32 with a gold alloy and 32 with a cobalt-chromium (Co-Cr) alloy. Over the bars' central area (8 × 3 mm 2 ), a bonding agent and two glass-ceramic layers were fired, totaling 1 mm in ceramic thickness. Eight specimens of each alloy were randomly divided according to the bonding agent (application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
1
1
0
1
Order By: Relevance
“…Addition of brass more than 20 wt.% was already able to change the natural properties of ceramic (brittle) in this study. This is supported by some previous research [23][24][25].…”
Section: Discussionsupporting
confidence: 89%
“…Addition of brass more than 20 wt.% was already able to change the natural properties of ceramic (brittle) in this study. This is supported by some previous research [23][24][25].…”
Section: Discussionsupporting
confidence: 89%
“…The results obtained by Lombardo et al (2010) [20] , Oliveira de Vasconcellos et al (2011) [40] , Oyafuso et al (2008) [41] and Fischer et al (2009) [49] were also similar to that reported in this research regarding reduction in the SBS values after thermomechanical cycling with significant differences. On the contrary, Antanasova et al (2018) [51] and Trindade et al (2014) [52] concluded that thermomechanical cycling decreased the bond strength for the ceramic to Co-Cr specimens but without statistically significant differences. This might be due to the difference in the thermodynamic protocols used in these two studies in comparison to the thermodynamic protocol used in this present study.…”
Section: Discussionmentioning
confidence: 98%
“…Araştırmacılar klinik olarak gerekli, kabul edilebilir ve uzun dönem başarılı kullanılabilecek makaslama dayanim değerinin 10 Mpa olması gerektiğini belirtmişlerdir. [21][22][23][24] Çalışmamızın sonuçlarına bakıldığında; Ultradent tamir sistemi grubu hariç tüm grupların dayanım değerleri klinik kabul edilebilir değer olan 10 MPa değerinden daha yüksektir. Literatür incelendiğinde; tamir sistemlerinin makaslama bağlanma dayanımlarını değerlendiren çalışmaların sonuçları 3 ile 37.4 MPa arasında değişmektedir.…”
Section: Gruplara Ait Kırılma Tiplerinin Gösterimiunclassified